2013
DOI: 10.1038/srep02667
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scale hydrogen-bond network improves the durability of greener cements

Abstract: More than ever before, the world's increasing need for new infrastructure demands the construction of efficient, sustainable and durable buildings, requiring minimal climate-changing gas-generation in their production. Maintenance-free “greener” building materials made from blended cements have advantages over ordinary Portland cements, as they are cheaper, generate less carbon dioxide and are more durable. The key for the improved performance of blends (which substitute fine amorphous silicates for cement) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…66 A similar result was also obtained for water in montmorillonite (hydrated clays) 67 and more recently in hydrated ordinary Portland cement where a decrease in the elastic intensity occurs at about 190 K and attributed to the activation of OH − motions. 68 In addition, studies on dried amorphous polysaccharides (cellulose and dextran) with two and three hydroxyl groups per ring, respectively, have shown on a weak relaxation similar to the here obtained process 1, however, with a somewhat higher activation energy of 0.33 eV. 69 Intriguingly, a similar fast process with a relatively low value of the activation energy is also found in other systems containing large amounts of hydroxyl groups such as, for instance, MCM-41 and various biological systems.…”
Section: Possible Molecular Origin Of the Fastest Relaxation In C-s-hmentioning
confidence: 99%
“…66 A similar result was also obtained for water in montmorillonite (hydrated clays) 67 and more recently in hydrated ordinary Portland cement where a decrease in the elastic intensity occurs at about 190 K and attributed to the activation of OH − motions. 68 In addition, studies on dried amorphous polysaccharides (cellulose and dextran) with two and three hydroxyl groups per ring, respectively, have shown on a weak relaxation similar to the here obtained process 1, however, with a somewhat higher activation energy of 0.33 eV. 69 Intriguingly, a similar fast process with a relatively low value of the activation energy is also found in other systems containing large amounts of hydroxyl groups such as, for instance, MCM-41 and various biological systems.…”
Section: Possible Molecular Origin Of the Fastest Relaxation In C-s-hmentioning
confidence: 99%
“…The term pozzolan has been extended to cover all siliceous/aluminous materials, which in finely divided form and in the presence of water, will chemically react with calcium hydroxide (CH) to form compounds with cementitious properties. Blended Portland cement production from the combustion of silicon-rich plant residues such as sugar cane bagasse ash, rice husk ash are reported elsewhere (25,(84)(85)(86)(87)(88)(89)(90)(91). The use of regional agro-industrial residues is a constructive way to save energy in transport and for a more simplified logistics to attend the global civil construction market.…”
Section: Natural Pozzolans As Mineral Additionmentioning
confidence: 99%
“…‡ 1 Gigatonne of carbon = 1 GtC = 1015 grams of carbon = 1 Petagram of carbon = 1 PgC. This corresponds to 3.67 GtCO 2 Cordeiro et al suggested that the sugar cane bagasse ash presents physico-chemical properties appropriate for its use as mineral addition and its reactivity was mainly dependent on particle size and specific surface area (87) Jacobsen et al (90) concluded that pozzolan reaction has promoted changes to the C-S-H structure so that it can interact more strongly with water molecules than a common C-S-H structure of an OPC paste.…”
Section: Natural Pozzolans As Mineral Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the world's increasing need is to control the global warming and environmental pollution minimizing the emission of the climate changing gasses (Jacobsen et al 2013;Phair 2006). It is stated in the Kyoto protocol 6 that including the carbon dioxide, some other gasses such as methane, nitrous oxide, sulfur dioxide, sulfur hexafluoride, hydrocarbons, chlorofluorocarbons, and perfluorocarbons, etc., are responsible for the greenhouse effect and global warming.…”
Section: Introductionmentioning
confidence: 99%